Chloroquine and Rapamycin Augment Interleukin-37 Expression via the LC3, ERK, and AP-1 Axis in the Presence of Lipopolysaccharides - Xiaoyi Shi; Chunhui Lai; Lianyu Zhao; Mingying Zhang; Xi Liu; Shanqin Peng; Weizhong Guo; Qiuying Xu; Song Chen; Guang-xing Chen (Journal of Immunology Research)
IL-37 is a cytokine that plays critical protective roles in many metabolic inflammatory diseases, and its therapeutic potential has been confirmed by exogenous IL-37 administration. However, its regulatory mechanisms remain unclear. U937 cells were treated with autophagy-modifying reagents (3-MA, chloroquine, and rapamycin) with or without LPS stimulation. Thereafter, IL-37 expression and autophagic markers (Beclin1, P62/SQSTM1, and LC3) were determined. For regulatory signal pathways, phosphorylated proteins of NF-κB (p65 and IκBα), AP-1 (c-Fos/c-Jun), and MAPK signal pathways (Erk1/2 and p38 MAPK) were quantified, and the agonists and antagonists of MAPK and NF-κB pathways were also used. Healthy human peripheral blood mononuclear cells were treated similarly to confirm our results. Four rhesus monkeys were also administered chloroquine to evaluate IL-37 induction in vivo and its bioactivity on CD4 proliferation and activation. IL-37 was upregulated by rapamycin and chloroquine in both U937 cells and human PBMCs in the presence of LPS. IL-37 was preferentially induced in autophagic cells associated with LC3 conversion. AP-1 and p65 binding motifs could be deduced in the sequence of the IL-37 promoter. Inductive IL-37 expression was accompanied with increased phosphorylated Erk1/2 and AP-1 and could be completely abolished by an Erk1/2 inhibitor or augmented by Erk1/2 agonists. In monkeys, chloroquine increased IL-37 expression, which was inversely correlated with CD4 proliferation and phosphorylated STAT3. IL-37 levels were induced by rapamycin and chloroquine through the LC3, Erk1/2, and NF-κB/AP-1 pathways. Functional IL-37 could also be induced in vivo.